Robust interference alignment algorithm for cognitive MIMO interference network - Shi-lei ZHU; You ZHOU; Xiu-kun REN; Han-ying HU (Tongxin xuebao)
A robust interference alignment algorithm was proposed for underlay cognitive MIMO interference network with imperfect channel-state information (CSI).Firstly,imperfect CSI was characterized by Euclidean ball-shaped uncer-tainty,based on which the optimization model of transmitting precoding and receiving interference subspace matrix was constructed with aimed of minimizing interference leak Then,primary users' interference temperature constraint un-der the worst-case condition was derived according to the matrix norm inequality.Finally,alternate iteration expressions of transceiver matrixes were obtained exploiting Lagrange partial dual-decomposition theory and sub-gradient update method.Moreover,the proposed algorithm's application condition and degrees of freedom range were theoretically ana-lyzed.Simulation results show that the proposed algor m is robust and its secondary users' network performance out-performs existing algorithms'.